The Aetiology of the Formation and Condensation of the Present Day Sand Hills - Asghari Moghadam, Mohammad Reza (International Journal of Bio-resource and Stress Management, 2011)
Sand hills are among the most amazing and the most beautiful sceneries of the arid and dry lands. They are caused by the process of removal of the soil from uneven surfaces and their movements to the margins. There are many factors involved in the process which encourage the question of whether this removal and replacement is accidental? and if not, what are the elements involved? Field studies show that there is always a direct relation between sand progression and the heights exposed to plains and playas. This means that higher the mountain, more the sand is drifted from the height, and vice versa. Therefore, it can be concluded that the difference between the heights of playa surfaces and that of the mountains causes temperature gradients and establishes a high pressure center over the heights. The temperature current which is produced from high pressure areas and moved to the lower levels prevents sand movement to the hillsides. On the other hand, the dominant currents which are flown from the surface of playa to the latitudes get diverted when they encounter latitudes at a level above the mountains, preventing the movement of sands. The exact place of the sands stalled is the meeting point of the counteracting currents, that is the dominant winds which pass the surface of playas and the local currents produced by the high pressure zones.